3w(w-6)-3=-3(-5w+5)-2w

Simple and best practice solution for 3w(w-6)-3=-3(-5w+5)-2w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3w(w-6)-3=-3(-5w+5)-2w equation:


Simplifying
3w(w + -6) + -3 = -3(-5w + 5) + -2w

Reorder the terms:
3w(-6 + w) + -3 = -3(-5w + 5) + -2w
(-6 * 3w + w * 3w) + -3 = -3(-5w + 5) + -2w
(-18w + 3w2) + -3 = -3(-5w + 5) + -2w

Reorder the terms:
-3 + -18w + 3w2 = -3(-5w + 5) + -2w

Reorder the terms:
-3 + -18w + 3w2 = -3(5 + -5w) + -2w
-3 + -18w + 3w2 = (5 * -3 + -5w * -3) + -2w
-3 + -18w + 3w2 = (-15 + 15w) + -2w

Combine like terms: 15w + -2w = 13w
-3 + -18w + 3w2 = -15 + 13w

Solving
-3 + -18w + 3w2 = -15 + 13w

Solving for variable 'w'.

Reorder the terms:
-3 + 15 + -18w + -13w + 3w2 = -15 + 13w + 15 + -13w

Combine like terms: -3 + 15 = 12
12 + -18w + -13w + 3w2 = -15 + 13w + 15 + -13w

Combine like terms: -18w + -13w = -31w
12 + -31w + 3w2 = -15 + 13w + 15 + -13w

Reorder the terms:
12 + -31w + 3w2 = -15 + 15 + 13w + -13w

Combine like terms: -15 + 15 = 0
12 + -31w + 3w2 = 0 + 13w + -13w
12 + -31w + 3w2 = 13w + -13w

Combine like terms: 13w + -13w = 0
12 + -31w + 3w2 = 0

Begin completing the square.  Divide all terms by
3 the coefficient of the squared term: 

Divide each side by '3'.
4 + -10.33333333w + w2 = 0

Move the constant term to the right:

Add '-4' to each side of the equation.
4 + -10.33333333w + -4 + w2 = 0 + -4

Reorder the terms:
4 + -4 + -10.33333333w + w2 = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -10.33333333w + w2 = 0 + -4
-10.33333333w + w2 = 0 + -4

Combine like terms: 0 + -4 = -4
-10.33333333w + w2 = -4

The w term is -10.33333333w.  Take half its coefficient (-5.166666665).
Square it (26.69444443) and add it to both sides.

Add '26.69444443' to each side of the equation.
-10.33333333w + 26.69444443 + w2 = -4 + 26.69444443

Reorder the terms:
26.69444443 + -10.33333333w + w2 = -4 + 26.69444443

Combine like terms: -4 + 26.69444443 = 22.69444443
26.69444443 + -10.33333333w + w2 = 22.69444443

Factor a perfect square on the left side:
(w + -5.166666665)(w + -5.166666665) = 22.69444443

Calculate the square root of the right side: 4.763868641

Break this problem into two subproblems by setting 
(w + -5.166666665) equal to 4.763868641 and -4.763868641.

Subproblem 1

w + -5.166666665 = 4.763868641 Simplifying w + -5.166666665 = 4.763868641 Reorder the terms: -5.166666665 + w = 4.763868641 Solving -5.166666665 + w = 4.763868641 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '5.166666665' to each side of the equation. -5.166666665 + 5.166666665 + w = 4.763868641 + 5.166666665 Combine like terms: -5.166666665 + 5.166666665 = 0.000000000 0.000000000 + w = 4.763868641 + 5.166666665 w = 4.763868641 + 5.166666665 Combine like terms: 4.763868641 + 5.166666665 = 9.930535306 w = 9.930535306 Simplifying w = 9.930535306

Subproblem 2

w + -5.166666665 = -4.763868641 Simplifying w + -5.166666665 = -4.763868641 Reorder the terms: -5.166666665 + w = -4.763868641 Solving -5.166666665 + w = -4.763868641 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '5.166666665' to each side of the equation. -5.166666665 + 5.166666665 + w = -4.763868641 + 5.166666665 Combine like terms: -5.166666665 + 5.166666665 = 0.000000000 0.000000000 + w = -4.763868641 + 5.166666665 w = -4.763868641 + 5.166666665 Combine like terms: -4.763868641 + 5.166666665 = 0.402798024 w = 0.402798024 Simplifying w = 0.402798024

Solution

The solution to the problem is based on the solutions from the subproblems. w = {9.930535306, 0.402798024}

See similar equations:

| 6x-2=x+13The | | 3[-2(4x+5)+4(5x-5)]= | | 63-4/9 | | -45+5x=6x+32 | | -95.31=x/3 | | 4/7*14/8(y-2) | | 11x-19=23 | | 4log(x)-6=2log(x) | | 23=5(x+3) | | 4lg(x)-6=2lg(x) | | gx=144 | | (x+1)(x-2)=(x-1)(x-1) | | -5/6=3/4n | | (3x-1)/(x-4)=0 | | 5x-8=3x-11+8 | | 2z-12-1=z-25+z | | 3/1728 | | 6(-2-3x)+8= | | -x-4=3x+6 | | -3-3x/21 | | 2(3m-9)-3(m-2)= | | 4x+5=8x+5 | | 7x-2=9x-4 | | 9x-9=19x-19 | | 11x-12=13x-20 | | 6x+3y=153 | | x+y=1.23 | | 5-x=32 | | 2x+15=13x+1 | | 10x+(12-x)=9x+12 | | 5x-1=10x-17 | | 19x+2=3x+14 |

Equations solver categories